Queer Relations: A Reading of Martha Nussbaum on Same-Sex Marriage - Jakobsen, Janet R. (Columbia Journal of Gender and Law, 2010)
This symposium on the work of Martha Nussbaum as part of the inauguration of the program on Gender and Sexuality Law at Columbia Law School provides a chance to reflect on the reasons for a focus on gender and sexuality in the study of the law. After all, one might ask, are questions of gender and sexuality-at least those beyond a few matters like discrimination-not private concerns that should rightfully be beyond the realm of the state and its laws? If we look at public policy over the past half-century, however, gender and sexuality have been central to a range of crucial questions of social policy as they have been enacted in law-from welfare reform to immigration policy to health care-and so it is crucial that this area be taken seriously in the study of law as well. As my way of phrasing this opening indicates, I am not a scholar of law, but rather of social policy and social movements, as these fields are understood within religious studies and through the lens of ethical analysis. I have used the tools of my training in social ethics and the study of religion to consider the role of gender and sexuality in contemporary U.S. policy. Martha Nussbaum’s extensive body of scholarship includes a focus on a range of social policies in conjunction with her explorations of constitutional law. Having written widely on questions of gender, Professor Nussbaum has more recently turned to sexuality as well, and her interest in constitutional law has taken her to a question that continues to roil both public discourse and public policy in the U.S.-same-sex marriage.